2017
DOI: 10.2214/ajr.16.16575
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Skipping of the Terminal Ileum in Pediatric Crohn Disease

Abstract: Ileocolonoscopy may miss SB CD in pediatric patients that is due to isolated histologic, intramural, or proximal inflammation. Enterography is complementary to ileocolonoscopy in the evaluation of pediatric CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…These features of CD lead to the need for SB imaging modalities like computed tomography enterography (CTE), magnetic resonance enterography (MRE), intestinal ultrasound (IUS), and capsule endoscopy (CE) [5,6], that have already been proven to alter management plans [7,8]. They should not be considered alternatives to ileocolonoscopy (IC) but complementary modalities able to detect proximal lesions [9]. These techniques are helpful in different settings in CD management, like in suspected CD, in patients with newly diagnosed CD, and in monitoring.…”
Section: Diagnostic Alternativesmentioning
confidence: 99%
“…These features of CD lead to the need for SB imaging modalities like computed tomography enterography (CTE), magnetic resonance enterography (MRE), intestinal ultrasound (IUS), and capsule endoscopy (CE) [5,6], that have already been proven to alter management plans [7,8]. They should not be considered alternatives to ileocolonoscopy (IC) but complementary modalities able to detect proximal lesions [9]. These techniques are helpful in different settings in CD management, like in suspected CD, in patients with newly diagnosed CD, and in monitoring.…”
Section: Diagnostic Alternativesmentioning
confidence: 99%
“…One study did not find any significant correlation between the time to peak and the endoscopic indices. This might be because the endoscopist can only visualize the mucosal surface and not the entire bowel wall, referred to as endoscopic skipping [ 56 ]. In addition, the intestinal vascular remodeling that occurs in IBD is characterized by formation of stenotic neo microvessels and thus impaired mucosal perfusion [ 24 ].…”
Section: Contrast-enhanced Ultrasound For Adults With Inflammatory Bowel Diseasementioning
confidence: 99%
“…A number of low-quality studies have demonstrated that completion of full ileocolonoscopy, including examination of the terminal ileum, is essential for the proper diagnosis and management of digestive diseases in most pediatric patients (51)(52)(53)(54). Incomplete or partial ileocolonoscopy, without inspection and tissue sampling of the ileocecal region, exposes pediatric patients to missed, misdiagnosed, and/or delayed diagnosis of IBD (55).…”
Section: 5%mentioning
confidence: 99%